Analysis and Comparison of the Theoretical Model of the Relationship between Reading and Writing - Ediwarman Ediwarman; Syafrizal Syafrizal; John Pahamzah (Makassar State University, 2022)
Abstract. This study compares and evaluates three alternative theoretical models of the relevant writing relationships. The reading dimensions of this model include components of understanding of places and parts. Dimensions include components of spelling, vocabulary, word structure, and story structure. These models differ with respect to the order in which the dimensions of reading and writing are related. The interactive model allows the use of reading knowledge in writing, and vice versa. Other models (read-to-write; write-to-read) only allow knowledge to move in one direction. These models are evaluated based on the model. The ability to explain the relationships found in the extensive corpus of reading and collecting data from 256 second graders and 251 fourth graders. The interactive model fits the data better than the read-to-write model at the second grade level and the write-to-read model at both grade levels and the read-to-write model are superior to the write-to-write model. Specific relationships are examined and pedagogical implications.Keywords: Analysis, Model Comparison, Reading, Writing.